Establishment of Long-Term Primary Cortical Neuronal Cultures From Neonatal Opossum Monodelphis domestica - Petrović, Antonela; Ban, Jelena; Tomljanović, Ivana; Pongrac, Marta; Ivaničić, Matea; Mikašinović, Sanja; Mladinic, Miranda (Frontiers in Cellular Neuroscience, 2021)
Primary dissociated neuronal cultures have become a standard model for studying central nervous system (CNS) development. Such cultures are predominantly prepared from hippocampus or cortex of rodents (mice and rats), while other mammals are less used. Here we describe the establishment and extensive characterization of the primary dissociated neuronal cultures derived from the cortex of the grey South American short-tailed opossums, Monodelphis domestica. Opossums are unique in their ability to fully regenerate their CNS after injury during their early postnatal development. Thus, we used cortex of postnatal day (P) 3-5 opossum to establish long-surviving and nearly pure neuronal cultures, as well as mixed cultures composed of radial glia cells (RGCs) in which their neurogenic and gliogenic potential was confirmed. Both types of cultures are able to survive for more than 1 month in vitro. We also prepared neuronal cultures from P16-18 opossum cortex, that were composed of astrocytes and microglia, in addition to neurons. The long-surviving opossum primary dissociated neuronal cultures represent a novel mammalian in vitro platform particularly useful to study CNS development and regeneration.